Town courts and urban society in late Medieval England, 1250-1500 - Goddard, Richard, 1967-; Phipps, Teresa (Suffolk, UK : The Boydell Press, 2019)
Town courts were the principal institution responsible for the delivery of justice and urban administration within medieval towns. Their records survive in large quantities in archives across England, and they provide an unparalleled insight into the lives and work of thousands of men and women who lived in these towns. The court rolls tell us much about the practice of law at the local level within towns, as well as yielding a broad range of perspectives on the economy, society and administration of towns. This volume is the first collection dedicated to the analysis of town courts and their records. Through a wide range of approaches, it offers new interpretations of the role that these courts played. It also demonstrates the wide range of uses to which court records can be put to in order to more fully understand medieval urban society. The volume draws on the records of a considerable number of towns and their courts across England, including London, York, Norwich, Lincoln, Nottingham, Lynn, Chester, Bromsgrove and Shipston-on-Stour.
Introduction / Richard Goddard and Teresa Phipps -- Jane Laughton : in memoriam -- Town courts in medieval England : an introduction / Maryanne Kowaleski -- Borough court cases as legal precedent in English town custumals / Esther Liberman Cuenca -- The Priest of Nottingham and the Holy Household of Ousegate : telling tales in court / Jeremy Goldberg -- Female litigants and the borough court : status and strategy in the case of Agnes Halum of Nottingham / Tersa Phipps -- Courts and urbanization : jurisdiction in late medieval seigneurial boroughs and towns / Christopher Dyer -- The business of the Leet Courts in medieval Norwich, 1288-1391 / Samantha Sagui -- The Black Death and the borough court : the changing pattern of social and judicial representation in late medieval Lincoln / Alan Kissane -- Justice and jurisdiction in late medieval Chester / Jane Laughton -- Trust : business networks and the borough court / Richard Goddard -- Society, status, and the Leet Court in Margery Kempe's Lynn / Susan Maddock -- Appendix: An annotated list of printed or online transcriptions and translations of medieval town courts in Britain to 1500 / Maryanne Kowaleski.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on August 05, 2019).
JSTOR
Keywords: Great Britain -- History -- Medieval period, 1066-1485.; Law, Medieval -- History -- To 1500.; Court records -- England -- History -- To 1500.; England -- Social conditions -- 1066-1485.; Urbanization -- England -- History -- To 1500.; Grande-Bretagne -- Histoire -- 1066-1485 (Moyen Âge); Angleterre -- Conditions sociales -- 1066-1485.; HISTORY -- Europe -- Great Britain; Law, Medieval; Court records; Social conditions; Urbanization; Great Britain; England; Justiz; Stadt; England; To 1500; Black Death; Chester; King's Lynn; Lincoln; Norwich; Nottingham; borough courts; borough customs; litigation; medieval England; medieval boroughs; medieval court rolls; medieval law; medieval towns; town courts; urban history; urban society; History